Ministerial Decree 661/2016 Amending Certain Provisions of Decree 209/2009 Concerning The Executive Regulations of Law 38/1977 On the Organization of Tourist Companies = قرار وزاري رقم 661 لسنة 2016 بتعديل بعض أحكام القرار رقم 209 لسنة 2009 باللائحة التنفيذية للقانون رقم 38 لسنة 1977 بتنظيم الشركات السياحية / Prime Minister - Egypt. Prime Minister (2025)
ministry of tourism decree no. 661 of the year 2016 issued on 21/7/2016 وزارة السياحة قرار رقم 661 لسنة 2016 صادر بتاريخ 21/7/2016